P-114 INVESTIGATING THE ROLE OF BOTOX IN THE EMERGENCY MANAGEMENT OF COMPLEX ABDOMINAL WALL HERNIAS. (13th October 2022) - Stevens, J; Kostalas, M; Chapman, A; Prabhudesai, S; Ratnasingham, K
Abstract: Aims: Botulinum toxin (Botox) has an established role in the elective management of complex abdominal wall hernia, but its role in the emergency setting has not been investigated. Clinical effects of Botox peak at 2–3 weeks after injection, but effects become apparent within 48 hours. We aimed to determine if these early effects can facilitate the acute reduction of irreducible hernia. Materials and methods: Patients with irreducible abdominal wall hernias over a 30 month period were considered for Botox therapy. Suitable patients were given 300 units of Botox under ultrasound guidance into the anterolateral muscles bilaterally. Data were collected on outcomes. Results: Twelve patients received Botox. All had incisional hernias and an ASA of 3 or more. Six were on antiplatelets and/or anticoagulation. All received Botox with standard conservative management. In ten patients, the hernia was reduced and symptoms resolved. One patient required surgery at 48 hours due to bowel ischaemia from inter-sac adhesions. A second patient experienced recurrent obstruction despite successful hernia reduction but was palliated due to advanced age and frailty. Conclusions: This case series is the first study to investigate the role of Botox in the acute management of irreducible hernias. Our findings suggest that in selected patients, Botox can aid hernia reduction and avoid the morbidity of emergency repair. This is of particular value in high risk patients and those with complex defects who benefit from preoperative optimisation techniques. The accurate identification of strangulation is crucial however, as it excludes patients from this approach.